Rethinking the causes of deforestation: lessons from economic models - Angelsen, A.; Kaimowitz, D. (1999)
This article, which synthesizes the results of more than 140 economic models analyzing the causes of tropical deforestation, raises significant doubts about many conventional hypotheses in the debate about deforestation. More roads, higher agricultural prices, lower wages, and a shortage of off-farm employment generally lead to more deforestation. How technical change, agricultural input prices, household income levels, and tenure security affect deforestation-if at all-is unknown. The role of macroeconomic factors such as population growth, poverty reduction, national income, economic growth and foreign debt is also ambiguous. This review, however, finds that policy reforms included in current economic liberalization and adjustment efforts may increase the pressure on forests. Although the boom in deforestation modeling has yielded new insights, weak methodology and poor-quality data make the results of many models questionable.